Design and Control of an Off Board Battery Charger for Electric Vehicles - Dar, Uzma; Siddiqui, Anwar Shahzad; Bakhsh, Farhad Ilahi (Distributed Generation & Alternative Energy Journal, 2022)
The rise in the penetration of electric vehicles has led to the increased interest in the charging technologies. Controlled charging and vehicle to grid power transfer is being given much importance. This paper proposes an off board charger (three phase) for charging the batteries used in electric vehicles. The proposed charger has a bidirectional power transfer capability so as to transfer power back to the utility grid. The topology proposed is simple and less costly as it has fewer elements. The charger has two converters, a three phase ac-dc converter for conversion of ac into dc and bidirectional dc-dc converter. The technique called Vector control is used to control ac-dc converter which allows controlling of active and reactive power independently. The control strategy proposed here provides a better control and leads to a better performance while maintaining unity power factor at input. The charging algorithm designed is such that it is able to maintain voltage at dc link at desired value. The charging algorithm is designed for lithium ion batteries and the combined Constant Current Constant Voltage (CC-CV) method of charging is used because it is simple and easy to implement. The proposed electric vehicle charger changes the mode of charging with change in State of Charge (SOC). The different modes are switched and the suitable reference is generated based on the different charging characteristics of a battery. The proposed charger is modeled in MATLAB-Simulink. The working operation of both forward and reverse power transfer mode has been analyzed. The proposed charger is able to maintain the unity power factor operation. The simulation results of all modes validate the design and control of the proposed charging topology.